Academic analysis of the indicators of the global innovation index (Research, Society and Development, 2022)
Given the importance of innovation in the economic growth effort of economies and the possibility of managing this process by governments, it is increasingly necessary to improve instruments that enable decision-making by managers. Among these are the indispensable metrics, since you cannot manage what you cannot measure. Within this context, this work seeks to verify if there is an academic support to justify the use of the specific 80 (eighty) indicators that make up the construction structure of one of the most important metrics of the level of innovation, called the Global Innovation Index - GII. This objective is pursued through extensive, but not exhaustive, bibliographic research, where it was possible to detect in the scientific literature at least 2 (two) publications that justify the selection by the builders of the GII - 2020 of each of the indicators. This result, in a way, complements the results of independent external audits, carried out annually, in the calculation of the indicators and their composite index in the effort to validate and generate credibility in the metric.